Maya Empire - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Surviving history., 2021)
Provides a series of questions that ask the reader to consider their life and choices as a member of Mayan culture and offers answers to whether or not they would have survived. Discusses what daily life was like, their human sacrifices, and various droughts and famines. Includes sidebars, resources for further study, and a glossary.